(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The breeding biology of Himalayan bulbul or white cheecked bulbul (Pycnonotusleucogenys) was studied in four transects of Southern landscape of kashmir valley in the year 2021-2022. During the course of study it was observed that 2 to 3 pale white base colors with dense pink speckles toward the broader end or brown spots were laid by the female during single nesting season. The eggs were oval in shape. The weight of one egg of seven days old was 3.10 gm. Average length and breadth of eggs were 17.8 mm ± 0.4378 and 13.6 mm ± 0.3373 (n=40). The mean weight of eggs collected from T3 (Seer) was found to be higher i.e., 3.25±0.30g and lower in the eggs of P. leucogenys collected from T2 (Hutmurah) i.e., 2.87± 0.63. 15 nests were found with 02 clutches, 02 nests were found with 03 clutches and four nests were found with 01 clutch. The incubation period of 11 to 14 days was recorded. The fledging period was recorded as 12 to 16 days. 40 eggs were laid by Pycnonotusleucogenys but only 8 nestlings were fledged. The breeding was poor but the hatching and fledging success was moderate. The breeding success rate was found to be on a higher side In case of aged and experienced breeding pairs and reduced breeding success in case of young and inexperienced breeding pairs. The breeding success was also affected by the density of the breeding pairs.